Marine phytoplankton improves recovery and sustains immune function in humans and lowers proinflammatory immunoregulatory cytokines in a rat model - Sharp, Matthew; Wilson, Jacob; Stefan, Matthew; Gheith, Raad; Lowery, Ryan; Ottinger, Charlie; Şahin, Kazım (Korean Society for Exercise Nutrition, 2021)
[Purpose] This study investigated the effects of marine phytoplankton supplementation (Oceanix®, Tetraselmis chuii) on 1) maximal isometric strength and immune function in healthy humans following a one-week high-intensity resistance-training program and 2) the proinflammatory cytokine response to exercise in a rat model. [Methods] In the human trial, 22 healthy male and female participants were randomly divided into marine phytoplankton and placebo groups. Following baseline testing, participants underwent a 14-day supplement loading phase before completing five consecutive days of intense resistance training. In the rat model, rats were randomly divided into four groups (n=7 per condition): (i) control, (ii) exercise, (iii) exercise + marine phytoplankton (2.55 mg/kg/day), or (iv) exercise + marine phytoplankton (5.1 mg/kg/day). Rats in the exercising groups performed treadmill exercise 5 days per week for 6 weeks. [Results] In the human model, marine phytoplankton prevented significant declines in the isometric peak rate of force development compared to placebo. Additionally, salivary immunoglobulin A concentration was significantly lower following the resistance training protocol in the placebo group but not in the marine phytoplankton group. Marine phytoplankton in exercising rats decreased intramuscular levels and serum concentrations of tumor necrosis factor-alpha (TNF-?) and interleukin-1 beta (IL-1?) and intramuscular concentrations of malondialdehyde. [Conclusion] Marine phytoplankton prevented decrements in indices of functional exercise recovery and immune function. Mechanistically, these outcomes could be prompted by modulating the oxidative stress and proinflammatory cytokine response to exercise. © 2021 Matthew Sharp et al.; © 2021 The Korean Society for Exercise Nutrition.
Keywords: antioxidant; cytokines; exercise recovery; immune function; immunoglobulin; muscle strength; oxidative stress